Hammertoe correction with wire fixation of varying length. Issue 8 (December 2022) - Mayolo, Patrick C.; Tran, Aaron; Kress, Kristen; Jaffe, David E.
Abstract: Background: Proximal interphalangeal (PIP) joint fusion with Kirschner (K) -wire fixation remains a popular strategy for hammertoe correction. This study was performed to evaluate the effect of length of wire fixation on clinical outcomes. Methods: A retrospective review of all hammertoe reconstructions by a single surgeon was performed. Wire length was chosen at the surgeon's discretion. Outcomes were assessed with metatarsophalangeal (MTP) congruency, pin complications, and PIP union. Results: 157 toes underwent reconstruction. Seventy had wires that spanned the MTP and 87 that did not. Wire breaks were significantly more common with longer wire fixation ( P = .024). MTP incongruency was significantly more common in the MTP group ( P = .014). Conclusion: Pin breakage was rare and only occurred in the MTP group. MTP incongruence was significantly more common in the MTP group but may not reflect surgical technique. PIP union was more common with longer wire fixation but is not clinically significant. Level of Evidence: III